1982
DOI: 10.1111/j.1399-3054.1982.tb04537.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation in Plantago major: Ca2+‐ and Mg2+‐stimulated ATPases from roots and their role in phenotypic adaptation

Abstract: The Mg2+‐ and Ca2+‐stimulated ATPase activities of the microsomal fractions of the roots of four inbred lines of Plantago major L. were followed at two levels of mineral nutrition. In addition the response of a transfer of plants from one condition to the other was studied. Kinetic properties of the ATPases (Km and Vmax) were calculated and used to differentiate between genetic differences among the inbred lines and the plasticity within each inbred line. The Vmax values of the ATPase activity differed signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…The same inbred lines also possessed different degrees of plasticity for the same characteristics. In an inbred line with a low seed number per capsule, viz P. major ssp major, a complete absence of plasticity was observed (Kuiper, 1982(Kuiper, , 1983. These results together with observations on P. major ssp major in this paper strongly suggest, that genotypes of P. major ssp major (seed number per capsule is ca ten) have no plasticity at all, not even during germination.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The same inbred lines also possessed different degrees of plasticity for the same characteristics. In an inbred line with a low seed number per capsule, viz P. major ssp major, a complete absence of plasticity was observed (Kuiper, 1982(Kuiper, , 1983. These results together with observations on P. major ssp major in this paper strongly suggest, that genotypes of P. major ssp major (seed number per capsule is ca ten) have no plasticity at all, not even during germination.…”
Section: Discussionsupporting
confidence: 79%
“…Characteristics ofthe nitrogen metabolism and of the energy metabolism (Lambers et al, 1981 b) were also shown to be rigid. In comparable experiments the Ca^"^-and Mg^+-stimulated ATPase activity from roots of this species did not change when the supply of mineral nutrients to the plants was increased or decreased (Kuiper, 1982;Kuiper and Kuiper, 1979a). Such a phenotypic rigidity was also found for morphological characteristics of P. major ssp major by Warwick and Briggs (1980).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Plants of four inbred lines, A3, GI, KI and Z2' were grown on two nutrient solutions, 100070 (114 strength Hoagland solution) and 2%; part of the plants were transferred from one to the other growth condition, halfway through the time of the experiment (Kuiper 1982). Plants of four inbred lines, A3, GI, KI and Z2' were grown on two nutrient solutions, 100070 (114 strength Hoagland solution) and 2%; part of the plants were transferred from one to the other growth condition, halfway through the time of the experiment (Kuiper 1982).…”
Section: Physiological Ecotype Differentiationmentioning
confidence: 99%
“…Plants of four inbred lines, A3, GI, KI and Z2' were grown on two nutrient solutions, 100070 (114 strength Hoagland solution) and 2%; part of the plants were transferred from one to the other growth condition, halfway through the time of the experiment (Kuiper 1982). A positive correlation between relative growth rate and the rapidity of the appearance of a plastic response (and completion of the plastic response) was demonstrated (Kuiper 1982 The results indicated that the involved genotypes probably typified a large scale of ecotype differentiation in P. major.…”
Section: Physiological Ecotype Differentiationmentioning
confidence: 99%